Sarcopenic obesity is associated with cardiometabolic multimorbidity in Chinese middle-aged and older adults: a cross-sectional and longitudinal study - Bingyan Yu; Shize Jia; Tiantian Sun; Jieliang Liu; Junguo Jin; Shanghong Zhang; Qiyao Xiao; Haojian Dong; Yanqiu Ou (Elsevier, 2024)
Objectives: Sarcopenic obesity (SO) has been found to increase the risk of metabolic disorders, however, its relationship with cardiometabolic multimorbidity (CMM) remains unexplored. This study aims to investigate the potential association between SO and CMM in the middle-aged and older population. Methods: Our study subjects were from CHARLS. SO was defined as the combination of impaired grip strength (grip strength <28 kg for men and <18 kg for women) and increased body mass index (BMI ≥25 kg/m2). CMM was defined as having two or more cardiometabolic diseases, including diabetes mellitus, stroke, and heart disease. The participants were divided into four groups according to their sarcopenia and obesity status, and logistic regression analysis was used to examine the association between SO and CMM. Results: A total of 15,252 study subjects were included in the cross-sectional study, with an average age of 60.6 years and a male proportion of 47.4%. In the cross-sectional analysis conducted in 2015, the prevalence of CMM was highest in the SO group (9.1%), followed by the obesity (3.7%) and sarcopenia (3.5%) group. After adjustment for confounding factors, SO [OR (95%CI): 2.453 (1.742−3.455)], sarcopenia [OR (95% CI): 1.601 (1.157−2.217)], obesity [OR (95% CI): 1.446 (1.107−1.888)] were all observed to be associated with CMM, with the strongest association in the SO group. Furthermore, in the longitudinal analysis, only the SO group demonstrated a significant risk for developing CMM [OR (95% CI): 2.302 (1.239−4.228)]. Conclusions: SO was independently and positively associated with CMM in middle-aged and older population.